Pelatihan Komputer Dasar Berbasis Aplikasi Microsoft Office bagi Siswa SMK Negeri 3 Merauke Provinsi Papua - Wahyuniar Wahyuniar; Desy Kumala Sari; Rezky Uspayanti (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this community service is to improve basic computer skills based on the Microsoft Office application for students of SMK Negeri 3 Merauke. This community service method used training with material presentation techniques and questions and answers. The training participants were 34 students of class X Multimedia Department. There were 2 (two) activities carried out, namely: the preparation of a Microsoft office training manual and a questionnaire response to training participants as well as the implementation of basic computer training activities online. The instruments used are response questionnaires and activity documentation. The results of this community service activity indicate that overall each indicator of the response of basic computer training participants is in the 'good' and 'very good' categories. The average percentage of responses is 98.23 which is included in the 'very good' category.